Comparative advantage and strategic specialization - Kang, Minwook (2019)
This paper shows that a strong comparative advantage is necessary for free trade and specialization in a 2 × 2 symmetric Ricardian model to be achieved in a Nash equilibrium. Governments strategically control labor distribution across industries, and representative agents maximize Cobb–Douglas utilities. A Nash equilibrium with complete specialization is achieved if and only if relative productivity exceeds a key value of 3, which is considered a very large number based on previous empirical studies. This paper also introduces a two‐stage game where each government chooses labor distribution first and then tariffs. In this two‐stage game, complete specialization is never achieved for any relative productivity level. Finally, by generalizing the Cobb–Douglas model into constant elasticity of substitution (CES) preferences, I show that if immiserizing growth effects exist, complete specialization could not be achieved for any level of relative productivity.